(untitled) (Research, Society and Development, 2024)
Mucormycosis is a rapidly progressive fungal disease, with greater rhinocerebral, pulmonary, specific and gastrointestinal involvement. It has destructive characteristics and high morbidity and mortality, and diagnosis and management should be effective, rapid and multidisciplinary. Most human infections result from inhalation of fungal sporangiospores that have been released into the air or from direct inoculation of organisms into damaged skin or mucosa, with Mucorales fungi being the main cause. Its association with COVID-19 has shown clinical relevance and some previous reports of coexistence. The objective of this study is to report two cases of acute invasive mucormycosis in the oral cavity of a post-COVID-19 patient in a hospital in the interior of the state of São Paulo. The reports may contribute to the early identification of the disease and provide technical information to assist in the treatment of patients affected by these diseases. We aim to expand knowledge and suggest the hypothesis that new studies should be carried out with the purpose of investigating transparency between acute invasive mucormycosis post-COVID-19.